Seismic induced flow disruption of Gandll K'in Gwaay.yaay thermal springs, Gwaii Haanas National Park Reserve, Canada. (April 2019) - Grasby, Stephen E.; Ferguson, Grant; Bartier, Patrick; Neville, Lisa
Abstract: The October 28, 2012 magnitude 7.8 Haida Gwaii earthquake disrupted flow of the only thermal springs in the Haida Gwaii archipelago of western Canada. Springs of the Gandll K'in Gwaay.yaay geothermal system ceased discharge at existing outlets and spring pools drained empty. Subsequent visits to the remote site documented return of flow at the lowest elevation discharge points, although at a greatly reduced discharge rate. Over time thermal water discharge was renewed at higher elevations and the total discharge rate increased. To understand better how seismic activity affected the spring flow, at a site ∼30 km distant from the epicentre, a study was initiated to inform development of a conceptual model of the thermal system. Stable isotope data show that thermal waters discharging at Gandll K'in Gwaay.yaay originate in deep circulation of meteoric waters, where they are heated by the normal increase in ground temperature with depth. Geothermal gradients in the region are relatively low, and aqueous geothermometry suggests that circulation depths of the system are ∼3.6 km. There is no significant difference in overall water geochemistry from before and after the earthquake, either suggesting that the flow path was clogged, or that changes in water pressure in the recharge zone have reduced the overall system drive. We propose a conceptual model, suggesting that the earthquake induced a drop in the water table of the recharge zone, reducing the driving force of the flow system, leading to flow cessation. As the water table returned back to normal elevations the spring system has begun to return to pre-earthquake discharge patterns. This interpretation is consistent with traditional knowledge of the site, were oral history records previous earthquake induced flow cessations and subsequent returns of spring flow. Highlights: Flow stoppage of thermal springs occurred in response to near-field earthquake. Gradual 5 year recovery is consistent with previous flow stoppages. Proposed model suggests seismic reduced pressure drive of the system.